Pharmacogenetics - Khalil, Islam A. (IntechOpen, 2021)
Pharmacogenetics is the study of the effects of individual genetics on drug responses. This book provides an overview of the current state of the pharmacological genetic aspects of these treatments. It discusses drugs with genetic information to support product labeling, clinical guidelines, or significant mechanical effects. Pharmacogenetic studies have also allowed us to better understand the pharmacology of medications used to treat neurologic and psychiatric disorders. This book also reviews the current state of the science and potential clinical utility of pharmacogenetic markers for these treatments. Furthermore, it highlights the in silico approach as a promising tool for further research on experimental pharmacology.